Pro Git - Chacon, Scott (Apress, 2012)
You’re about to spend several hours of your life reading about Git. Let’s take a minute to explain what we have in store for you. Here is a quick summary of this book’s nine chapters: In Chapter 1, you’ll cover Version Control Systems (VCSs) and Git basics—no technical stuff, just what Git is, why it came about in a land full of VCSs, what sets it apart, and why so many people are using it. Then, you’ll learn how to download Git and set it up for the first time if you don’t already have it on your system. In Chapter 2, you’ll go over basic Git usage—how to use Git in the 80% of cases you’ll encounter most often. After reading this chapter, you should be able to clone a repository, see what has happened in the history of the project, modify files, and contribute changes. If the book spontaneously combusts at this point, you should already be pretty useful wielding Git in the time it takes you to go pick up another copy......